Outcomes of Anatomical versus Functional Testing for Coronary Artery Disease - Douglas, Pamela S; Hoffmann, Udo; Patel, Manesh R; Mark, Daniel B; Al-Khalidi, Hussein R; Cavanaugh, Brendan; Cole, Jason; Dolor, Rowena J; Fordyce, Christopher B; Huang, Megan; Khan, Muhammad Akram; Kosinski, Andrzej S; et al. (The New England journal of medicine, 2015)
In a trial involving 10,003 patients with suspected coronary artery disease, clinical outcomes at 2 years were not improved with an initial strategy of CT angiography, as compared with functional testing (exercise ECG, nuclear stress testing, or stress echocardiography). New-onset, stable chest pain is a common clinical problem that results in approximately 4 million stress tests annually in the United States in ambulatory patients without diagnosed heart disease. 1 Despite advances in cardiac testing, there is scant information on health-related outcomes and little consensus about which noninvasive test is preferable. 2 – 4 As a result, current patterns of care have been questioned, including the testing of very-low-risk populations 5 and the catheterization of patients who do not have obstructive coronary artery disease (CAD). 6 – 8 The development of coronary computed tomographic angiography (CTA) and its application in this context has the potential to . . .